Development of a Transportation Miniature Educational Play Tool to Stimulate Higher-Order Thinking Skills (HOTS) among Group B Kindergarten Children at TK Negeri 5 Banda Aceh - sarmina; Fitirah Hayati; Mik Salmina (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aimed to develop a Transportation Miniature Educational Play Tool (APE) to stimulate Higher Order Thinking Skills (HOTS) among Group B children at TK Negeri 5 Banda Aceh. The study employed a Research and Development (R&D) method using the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects included a media expert, a material expert, a Group B teacher, and Group B children at TK Negeri 5 Banda Aceh. Data were collected through observation, questionnaires, and documentation. The research instruments consisted of media expert validation sheets, material expert validation sheets, teacher response questionnaires, and observation sheets for assessing children's HOTS. The results indicated that the developed Transportation Miniature APE met the criteria of being highly valid, as evidenced by media and material expert validation scores that reached 100% after revisions. Teacher responses also showed that the media was practical and easy to use in the learning process. Furthermore, the use of the Transportation Miniature APE increased children's engagement in activities such as observing, classifying, comparing, analyzing, and solving simple problems, which are indicators of HOTS. Therefore, the Transportation Miniature APE was found to be valid, practical, and effective, making it suitable for use as a learning medium to stimulate higher-order thinking skills among Group B children at TK Negeri 5 Banda Aceh.